Manfaat Media Digital Bagi Katekis Sebagai Sarana Berkatekese Kepada Kaum Muda - Maria Sudri Yanti Dhiu; Intansakti Pius X (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
Digital technology is increasingly developing and becoming an important part of everyday life. In the world of catechesis, digital media can be used to increase young people's interest and understanding of religious teachings. Young people are the millennial generation who are very active in utilizing digital media. Catechists see digitalization as an opportunity to develop catechesis further. Catechists must know and use digital devices, not only as personal communication tools, but also as tools for catechesis to the congregation, especially young people. By using digital media to give catechesis young people can be involved in the church and they can feel God's greeting and presence in their lives. Therefore, catechists must really understand how to use digital media so that preaching attracts the attention of young people. This article discusses the various benefits of using digital media such as ease of access, interactivity, and flexibility in conveying religious messages. Apart from that, this article also discusses the challenges and ways to overcome problems that arise in the use of digital media in catechesis for young people. In conclusion, digital media can be an effective to catechesis for young people and needs to be developed taking into account the challenges and positive aspects of its use.